Applications of tandem mass spectrometry (MS/MS) in antimicrobial peptides field: Current state and new applications - Panpan Fang; Songlin Yu; Xiaoli Ma; Lian Hou; Tiewei Li; Kaijie Gao; Yingyuan Wang; Qianqian Sun; Lujun Shang; Qianqian Liu; Manjie Nie; Junmei Yang (Heliyon, 2024)
Antimicrobial peptides (AMPs) constitute a group of small molecular peptides that exhibit a wide range of antimicrobial activity. These peptides are abundantly present in the innate immune system of various organisms. Given the rise of multidrug-resistant bacteria, microbiological studies have identified AMPs as potential natural antibiotics. In the context of antimicrobial resistance across various human pathogens, AMPs hold considerable promise for clinical applications. However, numerous challenges exist in the detection of AMPs, particularly by immunological and molecular biological methods, especially when studying of newly discovered AMPs in proteomics. This review outlines the current status of AMPs research and the strategies employed in their development, considering resent discoveries and methodologies. Subsequently, we focus on the advanced techniques of mass spectrometry for the quantification of AMPs in diverse samples, and analyzes their application, advantages, and limitations. Additionally, we propose suggestions for the future development of tandem mass spectrometry for the detection of AMPs.